Effect of modular teaching method on democratic values of Grade VIII students - Singh, Somu; Rathore, H.C.S. (JOURNAL OF INDIAN EDUCATION, 2013)
This study reports the effect of modular teaching method as compared to traditional teaching methods on democratic values of grade VIII students. Adopting the quasi-experimental, non-equivalent control group design, the experiment was conducted on two intact grade VIII classes in an elementary school of Mirzapur, UP. The modules prepared by researcher served as the content for the experimental group. The results revealed that the democratic values post test scores of the treatment group had higher estimated marginal means than the control group. Levene’s test showed that the homogeneity of variance between the two groups was met for democratic values posttest scores. The univariate effect for democratic values post test scores was significant. The conclusion was that the modular teaching method was more effective for developing democratic values as compared to traditional teaching method.